Peran Pengrajin Songket Dalam Meningkatkan Pendapatan Sektor Ekonomi Kreatif ditinjau dari Perspektif Etika Bisnis Islam - Salim, Amir; Nopiansyah, Doly; -, Masruchin (Islamic Economics Department, Faculty of Islamic Economics and Business, UIN SULTHAN THAHA SAIFUDDIN JAMBI, 2023)
Songket craftsmen play an important role in supporting regional income thorough creative economy in Palembang city. This study aims to analyze the role of the creative economy to increase the income of songket craftsmen from the perspective of Islamic business ethics. This type of research is field research that uses descriptive qualitative methods with data collection techniques using interviews and documentation methods, all of which will be analyzed inductively. The results showed that the role of the creative economy carried out by songket craftsmen in Palembang city is (1) Increasing new innovations that consumers want so that their products are not left behind in accordance with the times, (2) Increasing income, (3) Contributing to the creation of new jobs. Creative activities in songket craftsmen use the principles of Islamic business ethics in terms of managing, caring, benefiting each other, and being responsible for what is done.